Modulation of spray droplet number density and size distribution by an acoustic field. (March 2017) - Achury, Javier; Polifke, Wolfgang
Multiple interactions may occur when a poly-disperse spray is exposed to an acoustic field. In the context of spray combustion instabilities, acoustic agglomeration, the formation of a droplet number density wave and the modulation of the droplet size distribution are interesting effects. A droplet number density wave, i.e. preferential concentration of droplets in space, may result from size-dependent, one-way momentum coupling between the acoustic field and the spray. The modulation of the droplet size distribution, which has been evidenced in the experimental work of Gurubaran and Sujith (AIAA 2008-1046), is thus a consequence of the droplet number density wave formation. In the present work, the mechanisms that produce these effects are simulated and analyzed in depth by means of computational fluid dynamics. The spray is modeled with both Lagrangian (particles mass-point approach) and Eulerian (continuous phase approach) descriptions. The particular Eulerian method used is a variant of the presumed density function method of moments, which allows to account for the effects of poly-dispersity, in particular the size-dependence of particle velocity. Both the Lagrangian and Eulerian models are validated against experimental data for spray dynamics and spray response to an acoustic field.